PENGARUH PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PELAKSANAAN PEMBANGUNAN DI DESA TIMBUKAR KECAMATAN SONDER - Lombogia, Ribka; Ruru, Joorie Marhaen; Plangiten, Novva (Sam Ratulangi University, 2018)
The participation of the community in the implementation of development is less visible; almost all thepeople do not participate in the implementation of development either in the form of community activenessin the implementation of development, willingness to donate thoughts or ideas, skills, time, energy andresponsibility to the success of development. Lack of public participation in the implementation ofdevelopment because the government lacks socialization, communication, motivation and even developmentplans are not in accordance with the wishes of the community. This study is to answer the magnitude of theEffect of Public Participation on the Effectiveness of Development Implementation in Timbukar VillageSonder Sub District of MinahasaThis research is a quantitative research that is trying to answer the magnitude of the influence of communityparticipation variable on the effectiveness variable of development implementation. Sampling in this studyis intended to obtain data or the whole of the population, a large sample of 55 respondents. Data analysistechniques use simple linear regression and Pearson Product Moment Correlation AnalysisResult of research Public participation have significant or strong influence to effectiveness of developmentimplementation, where the value of correlation coefficient (r) = 0,720 whereas coefficient of determination(rÂ²) = 0, 5184 or 51, 84%. So, the more often the community implements the participation of the communitythen the effectiveness of the implementation of development will increaseKeywords: Community Participation, Effectiveness and Development